solve for x 1,4 (x+2) = 5,6?

Guide :

solve for x 1,4 (x+2) = 5,6?

1/4 (one fourth) (x+2)= 5/6 (five sixths) {2/3, 3/4, 5/4, 4/3}

Research, Knowledge and Information :


x^2-x-6=9 - Equation Calculator - Symbolab


Equation Calculator Solve linear, quadratic, biquadratic. absolute and radical equations, ... 5x-6=3x-8; x^2-x-6=0; x^4-5x^2+4=0 \sqrt{x-1}-x=-7 \left|3x+1\right|=4
Read More At : www.symbolab.com...

Solve for x - Math Central


I can never seem to solve the "RESOLVE X ... The English would be "Solve for X" or "Find ... (x-1) becomes x+5 = 2(x-1) (divide by 3) (3x-1)/2 = 4 becomes 3x ...
Read More At : mathcentral.uregina.ca...

How do you solve (x-2)/3+1/6=5/6? | Socratic


x=4 (x-2)/3+1/6=5/6 (x-2)/3+1/6-5/6=0 ... How do you solve #(x-2)/3+1/6=5/6#? Algebra. 1 Answer ... How do you solve #lnx=-1#?
Read More At : socratic.org...

Solving One-Step Linear Equations (page 2 of 4) - Purplemath


Solving One-Step Linear Equations (page 2 of 4) Sections: One ... Solve x / 5 = –6; Since the x is divided by 5, I'll want to multiply both sides by 5:
Read More At : www.purplemath.com...

Simplifying versus Solving - Purplemath | Home


Simplifying versus Solving ... For instance: Solve 3 + 2[4x – (4 + 3x)] = –1; As usual, ... –18x + 34. Solve 2(x + 3) = 4 ...
Read More At : www.purplemath.com...

www.webmath.com


The problem to solve is: 2 (x + 4) + 4 (x - 6)=80 First, let's work on the left hand side of your equation, the 2 (x + 4) + 4 (x - 6) This means, for instance, ...
Read More At : www.webmath.com...

solve linear equation w/many operations


solve linear equation w/many operations ... 1 8.) 3x + 4(x -1) = 2 Solve equations which require undoing many operations, some on each side. 9.) 3 + 2x = 4x - 1
Read More At : www.mathnstuff.com...

5 Ways to Solve for X - wikiHow


How to Solve for X. There are a number of ways to solve for x, ...
Read More At : www.wikihow.com...

Untitled Document [www.math.brown.edu]


... Factor x 2 - 4x + 4 How to solve quadratic equations; quadratic formula Ex: ... = x 5 - 2x 4 + 4x 2 + 4x 4 - 8x 3 + 16x - x 3 + 2x 2 - 4 (x 2 + 4x - 1)(x 3 - 2x 2 ...
Read More At : www.math.brown.edu...

6 ÷ 2 (2 + 1) = CORRECT WAY TO SOLVE - YouTube


Apr 30, 2011 · 6 ÷ 2 (2 + 1) = CORRECT WAY TO SOLVE helperRobo. Loading... Unsubscribe from helperRobo? Cancel Unsubscribe. Working... Subscribe Subscribed Unsubscribe ...

Suggested Questions And Answer :


How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving
Read More: ...

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

How do you solve this problem? solve for d: n= m+3d/4

Problem: How do you solve this problem? solve for d: n= m+3d/4 I need help solving this and seeing how it was solved since I am having trouble figuring out what to do and how to solve it thanks. n = m + 3d/4 n - m = (m + 3d/4) - m n - m = 3d/4 4(n - m) = (3d/4)4 4(n - m) = 3d 4(n - m)/3 = 3
Read More: ...

Solve, using linear combination. 3x + y = 4 2x + y = 5

line 1: 3x+y=4    or y=4-3x line 2: 2x+y=5 line 1 -line2...(3x-2x)+(y-y)=4-5 or x=-1 y=4-3x=4+3=7
Read More: ...

how can i solve these equations?

how can i solve these equations? x + 3y – z = 2 x – 2y + 3z = 7 x + 2y – 5z = –21 We eliminate one of the unknowns (x, y or z, take your choice), leaving two unknowns. Then, we eliminate a second one, giving us an equation with only one of the unknowns. Solve for that and plug that value in
Read More: ...

Inequalities

9x+6=51 9x=51-6 9x=45 x=5
Read More: ...

how do you solve 3/x+5

how do you solve 3/x+5 I'm confused on how to solve this problem All you have is an expression. There is nothing to solve until you make it an equation. 3/x + 5 = -8 3/x + 5 = 14 3/x + 5 = 0 3/x + 5 = 38.67 3/x + 5 = -91 3/x + 5 = 43 Those can be solved, because they are complete. Each one will h
Read More: ...

x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)
Read More: ...

how to solve by substitution

how to solve by substitution .3x+3y=1.2(100) "Substitution" implies there are TWO equations in two unknowns. You solve one of them for one of the unknowns in terms of the other, e.g., solve for y in terms of x. THEN, you substitute that value into the other equation where the y is, and yo
Read More: ...

2x+y=9 x-2z=-3 2y+3z=15

2x+y=9 x-2z=-3 2y+3z=15 Forgot how to do This. Problems Solving systems of this type requires eliminating all but one unknown so you can solve for that unknown. Then, plug that value into one of the equations to solve for another of the unknowns. Finally, plug both of those values into an equation
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0681 seconds